Pengelolaan Pembelajaran IPA Kelas V di SDN Gambirsari Surakarta - Kristiani, Dewi, Prof. Dr. Sutama ,M.Pd, Dr. Sofyan Anif (2016)
Twenty first century is transformation era for education world. Related to education transformation, the teacher should attempt to shift the learning management paradigm from teacher-oriented to student-centered one. This research aimed to describe the management of Natural Science Learning in the 5th graders of SD Negeri Gambirsari Surakarta concerning planning, implementing, and evaluating. This research employed a descriptive qualitative method with ethnographic approach. Techniques of collecting data used were interview, observation, and documentation. The data analysis was conducted using an interactive model of analysis encompassing four steps: data collection, data reduction, data display, and data verification. Data validation was carried out using source triangulation technique and method. From the result of research, it could be concluded that the planning involved developing learning set, determining learning method, media, and approach, and preparing visual aids. Learning set consisted of Annual Program, Semester Program, Syllabus and Learning Implementation Plan. The implementation consisted of three steps: preliminary, main, and closing activities. Main activity was divided into three: exploration, elaboration, and confirmation. Evaluation was divided into three: cognitive, affective and psychomotor.